PERFORMANCE MEASUREMENT OF GREEN SCM WITH SCOR APPROACH TO REDUCE POLLUTION IN MSMES - Ahistasari, Asih; Gani, Mardhiah; Faradillah, Jihan Muhrifa; Wahyudien, Mohammad Arief Nur; Rachmadhani, Mirga Maulana (Center for Study and Journal Management FTI UMI, 2024)
Micro, Small, and Medium enterprises (MSMEs) play an essential role in the Indonesian economy, contributing 61.97% to GDP and absorbing 97% of the workforce. However, MSME production also impacts environmental pollution due to limited knowledge and technology. This study aims to identify performance measurement indicators and develop a measurement model combining Green Supply Chain Management (GSCM) and Supply Chain Operations Reference (SCOR). This model focuses on integrating environmental aspects in the supply chain to reduce negative impacts during the product life cycle. This research method combines GSCM and SCOR which include processes (plan, source, make, delivery, return, waste), to produce performance measurements. The study results can provide recommendations for the government and MSME actors, especially in Sorong, in managing the supply chain sustainably and minimizing environmental impacts.